(untitled) (University of Khartoum Engineering Journal, 2022)
Fluoride removal from water is one of the topics that researchers have discussed frequently in the recent period. Many techniques were invented; however; adsorption is considered the most preferred one due its high efficiency low cost. Aluminum Oxide Coated Charcoal AOCC is the one of the most promising fluoride adsorbent. Different researchers found that; AOCC are not only recovering its adsorption capacity after regeneration; but amazingly the adsorption capacity is further increase. The aim of this study is to investigate the reason behind the enhancement of AOCC adsorption capacity after regeneration and to optimize its coating process. Different coating conditions were applied then batch experiments were performed to determine the isotherms and kinetics of fluoride adsorption onto AOCC. Moreover, different techniques were used to characterize the adsorbent such as SEM, EDX and pH point of zero charge methods. The results show that incorporation of fluoride into coating process resulted in formation of aluminum hydroxide precipitates inside the charcoal pores. This precipitated aluminum hydroxide particles lead to enhance the specific surface area and increase the aluminum contents in adsorbent which consequently improve fluoride adsorption capacity.